2018
DOI: 10.5812/jjm.74315
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Antibiotic Resistance Phenotypes and Biofilm Formation Capacity in Clinical Isolates of Acinetobacter baumannii

Abstract: Background: Understanding of the biological factors responsible for prevalence and persistence of Acinetobacter baumannii in hospital settings is critical to prevent and control the corresponding nosocomial infections. Objectives: This study was conducted to investigate whether the biofilm-forming ability is associated with the emergence of different antibiotic resistance phenotypes [multidrug resistance (MDR)/extensively drug resistance (XDR) and non-MDR] of A. baumannii. Methods: The capacities of biofilm fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…isolate 1 was resistant to tigecycline and minocycline. These findings were similar to those of Rahimi et al [19], who reported that the isolated Acinetobacter spp. were sensitive to polymyxin E. In addition, 94% and 73% of isolates were sensitive to tigecycline and minocycline.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…isolate 1 was resistant to tigecycline and minocycline. These findings were similar to those of Rahimi et al [19], who reported that the isolated Acinetobacter spp. were sensitive to polymyxin E. In addition, 94% and 73% of isolates were sensitive to tigecycline and minocycline.…”
Section: Discussionsupporting
confidence: 92%
“…A complete picture of antibiotic resistance for the tested isolates was created according to the criteria outlined by Magiorakos et al [27]. Our results agree with the data of Rahimi et al [19], who found that 76% of Acinetobacter spp. isolates exhibited an XDR phenotype.…”
Section: Discussionsupporting
confidence: 90%
“…However, carbapenem-resistant strains of A. baumannii are increasing. Hence, it is essential to limit the use of these antibiotics [ 5 14 15 16 ]. In the current study, 170 CRAB isolates were collected from two hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Rahimi et al found that biofilm-producing P. aeruginosa had comparatively higher resistance to amikacin than non-biofilm-forming strains. Also, MDR/XDR strains show a strong relationship between biofilm formation and antibiotic resistance [21].…”
Section: Discussionmentioning
confidence: 99%